Fractional order sliding mode control of wind turbines based on wind speed estimator - Zoubaa, Yassamine; Chouiekh, Sihame; El Bakri, Ayoub; Boumhidi, Ismail (2023 14th International Conference on Intelligent Systems: Theories and Applications (SITA), 2023)
In this paper, a maximum power point tracking (MPPT) control system is proposed for wind power conversion using a new robust fractional order sliding mode controller (FOSMC) based on a wind speed estimator. The proposed approach does not rely on assumptions about uncertainties, disturbances, or their bounds, but instead utilizes a continuous control strategy to achieve chattering-free fractional order sliding-mode control. The FOSMC control follow the desired signal with good performance in the presence of the aerodynamic uncertainties. Lyapunov's stability theory is employed to demonstrate the boundedness and convergence properties of the closed-loop signals. Simulation results are presented to evaluate the effectiveness and robustness of the proposed control approach under various uncertainties, using a realistic wind speed profile.